Study of high resolution ro-vibrational spectra of the CH2=CD2 molecule: set of the lowest fundamental bands; High Resolution Molecular Spectroscopy, HRMS - Ulenekov (Ulenikov) O. N. Oleg Nikolaevich; Gromova O. V. Olga Vasilievna; Bekhtereva E. S. Elena Sergeevna; Beryozkin K. B. Kirill Borisovich; Kashirina N. V. Nadezhda Vladimirovna; Bauerecker Z. (S.) H. Zigurd (Sigurd) Hermann; Sydow C.; Tan T. L. (Poster Session D, 2015)
Title screen